Modelling of sediment diagenesis and its linkage with the water column. the case study of bay of quinte, Canada - Phuong T.K. Doan (Tạp chí Khoa học và Công nghệ)
In this study, the Aquasim model has been applied and developed to simulate the processes occurring in the sediments of the eutrophic system at Quinte Bay, Canada. The findings reveal that phosphorus (P) retention varies both spatially and temporally across the three basins of the Bay. These variations are influenced by factors such as sedimentation history, the chemical form of P, topography, and historical land use. According to the model, recent data indicates a decline in accumulated P at two shallow sediment sites (B and N), potentially leading to increased P release from these sediments. In contrast, the deeper sediment site (HB) continues to show high and stable P accumulation, resulting in consistently low and relatively unchanged P release. This explains why P levels in the Bay remain high, contributing to the growth of algae. The study also highlights the importance of adequately reducing external P loading. Internal P loads only play a supportive role in achieving the desired ecological conditions of the Bay.